Catalyzing sustainability pathways: Navigating urban nature based solutions in Europe. (May 2022) - Tozer, Laura; Bulkeley, Harriet; van der Jagt, Alexander; Toxopeus, Helen; Xie, Linjun; Runhaar, Hens
Highlights: Forging sustainability pathways depends on catalyzing change rather than scaling up. We conceptualize how sustainability transition pathways emerge from catalytic change. We argue aligning clusters of interventions builds momentum that generates sustainability pathways. Accelerating uptake of urban nature-based solutions in Europe can be supported by 20 interventions. Normalizing experiments is key to mainstreaming these responses to sustainability challenges. Abstract: The notion that pathways can be identified and followed towards more sustainable futures has become an increasingly prevalent idea across the science and policy of global environmental change. Focusing on the debate within literatures on socio-technical systems, we find that pathways are often tied to the concept of scaling up such that they are dependent on trajectories which extend from the geographically small to large scale or from singular incidences to widespread adoption. Building on relational approaches to scaling, in this paper we argue that sustainability pathways need to be conceived as emerging from the catalytic interaction of multiple and overlapping efforts to change the status quo. We suggest that pathways can be conceptualized as being composed of 'stepping stones': bundles of related interventions that seize or create opportunities to build momentum for the implementation of innovations, the form of which is not predetermined. Drawing on 243 interviews, participant observation, and document analysis examining urban nature-based solutions across six European countries and the EU, we identify 20 stepping stones that can be used to accelerate the uptake of urban NBS in European cities. In the case of urban NBS in Europe, we find that the capacity of stepping stones to generate catalytic change strongly depends on how they interact with one another. We illustrate that pathways are not given but rather assembled through key interventions that collectively generate the capacities and momentum needed to overcome inertia and generate new socio-material orders in which such interventions are normalized as mainstream responses to sustainability challenges.